2009
DOI: 10.1097/mnm.0b013e328319bfcc
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial adrenergic innervation in patients with vasovagal syncope measured with 123I-MIBG uptake

Abstract: In our patients with VVS, global I-MIBG deficit was present frequently, and all patients had regional adrenergic nerve function deficit. These alterations may play a role in causing clinical symptoms and have importance in staging and treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…123-I-MIBG scanning has previously shown higher H:M ratios in head-up tilt positive paediatric patients with vasovagal syncope [ 11 ], though an uncontrolled study in adult vasovagal patients showed more variable regional uptake deficits [ 12 ]. A more recent study in 60 patients with vasovagal syncope and 20 controls found lower H:M ratios in the vasovagal patients though with highly variable adrenergic innervation deficits in the left ventricular myocardium [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…123-I-MIBG scanning has previously shown higher H:M ratios in head-up tilt positive paediatric patients with vasovagal syncope [ 11 ], though an uncontrolled study in adult vasovagal patients showed more variable regional uptake deficits [ 12 ]. A more recent study in 60 patients with vasovagal syncope and 20 controls found lower H:M ratios in the vasovagal patients though with highly variable adrenergic innervation deficits in the left ventricular myocardium [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated diminished sympathetic innervation and function in patients with HUUT+. 36 In addition, there is evidence regarding the cardiac sympathetic role in myocardial contractility. 37,38 On the other hand, sympathetic nerves are involved in VVS.…”
Section: Discussionmentioning
confidence: 99%